(untitled) (Journal of Applied Oral Science, 2016)
Artificial bone has been employed to reconstruct bone defects. However, only few reports on implant placement after block bone grafting exist. Objectives The purpose of this study was to evaluate the osseointegration of dental implant in bone reconstructions with interconnected porous calcium hydroxyapatite (IP-CHA). Material and Methods The IP-CHA cylinders (D; 4.3 mm, H; 10.0 mm) were placed into bone sockets in each side of the femurs of four male dogs. The IP-CHA on the right side was a 24-week sample. Twelve weeks after placement, a titanium implant was placed into a socket that was prepared in half of the placed IP-CHA cylinder on the right side. On the left side, another IP-CHA cylinder was placed as a 12-week sample. After another 12 weeks, the samples were harvested, and the bone regeneration and bone-implant contact (BIC) ratios were measured. Results New bone formation area was superior in the 24-week IP-CHA compared with the 12-week IP-CHA. BIC was not significantly different between IP-CHA and the parent sites. Osseointegration was detected around the implant in IP-CHA-reconstructed bone. Conclusion Our preliminary results suggest that IP-CHA may be a suitable bone graft material for reconstructing bones that require implant placement.